Tell me your story and I will tell you who you are: Persona perspective in sustainable consumption. Issue 10 (24th July 2018) - Onel, Naz; Mukherjee, Avinandan; Kreidler, Nicole Bieak; Díaz, Estela M.; Furchheim, Pia; Gupta, Shipra; Keech, Jessica; Murdock, Mitchel R.; Wang, Qin
Abstract: Although research in marketing and consumer behavior has tried to portray sustainable consumers in many different ways, a clear, consistent, and granular identification of these consumers is still not available due to the complexity of sustainable consumption. This study adopts personas as a way to better explain and understand the holistic nature and complexity of sustainable consumer behavior in terms of its various stages (i.e. acquisition, usage, and postuse) within four key behavioral functions of mobility, housing, clothing, and food. Different sustainability related functions of personas are seen to be fundamental lifestyle components and could be fulfilled by a variety of sustainable actions. This exploratory study uses a qualitative methodology, involving data collection through multiple in‐depth interviews across several countries. The results reveal three different consumer archetypes with distinct sustainable consumption strategies: holistic sustainable consumers, transitional sustainable consumers, and restricted sustainable consumers. Managerial and theoretical implications provide practical recommendations for marketing managers and public policy planners, as well as directions for continued research in this area.